2017
DOI: 10.1007/s11064-017-2307-8
|View full text |Cite
|
Sign up to set email alerts
|

Microglial Interferon Signaling and White Matter

Abstract: Microglia, the resident immune cells of the CNS, are primary regulators of the neuroimmune response to injury. Type I interferons (IFNs), including the IFNαs and IFNβ, are key cytokines in the innate immune system. Their activity is implicated in the regulation of microglial function both during development and in response to neuroinflammation, ischemia, and neurodegeneration. Data from numerous studies in multiple sclerosis (MS) and stroke suggest that type I IFNs can modulate the microglial phenotype, influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 118 publications
2
31
0
Order By: Relevance
“…An outstanding feature of differential response of aged animals to ischemic stroke was upregulation of IFN-I pathway ( Figure 2B, 3A, 5A-E, S2, S3B), which persisted for at least 14 days ( Figure 6E). IFN-Is are antiviral cytokines with pleiotropic roles 129 implicated in a number of CNS pathologies including multiple sclerosis 130,131 , Aicardi-Goutières syndrome, amyotrophic lateral sclerosis 132 , Alzheimer's disease 59,133,134 , spinal cord injury 135 , traumatic brain injury 136,137 and ischemic stroke 100,103,138 . Therefore, we have explored INF-I signaling in more detail and found that two IFN-I regulatory modules are activated by stroke irrespective of age, but only the canonical STATdependent module is differentially activated in aged animals ( Figure 6B-D), likely contributing to an increased neurotoxicity 100 .…”
Section: Discussionmentioning
confidence: 99%
“…An outstanding feature of differential response of aged animals to ischemic stroke was upregulation of IFN-I pathway ( Figure 2B, 3A, 5A-E, S2, S3B), which persisted for at least 14 days ( Figure 6E). IFN-Is are antiviral cytokines with pleiotropic roles 129 implicated in a number of CNS pathologies including multiple sclerosis 130,131 , Aicardi-Goutières syndrome, amyotrophic lateral sclerosis 132 , Alzheimer's disease 59,133,134 , spinal cord injury 135 , traumatic brain injury 136,137 and ischemic stroke 100,103,138 . Therefore, we have explored INF-I signaling in more detail and found that two IFN-I regulatory modules are activated by stroke irrespective of age, but only the canonical STATdependent module is differentially activated in aged animals ( Figure 6B-D), likely contributing to an increased neurotoxicity 100 .…”
Section: Discussionmentioning
confidence: 99%
“…Interferons (IFNs) are naturally occurring cytokines, and their effects on the periphery as well as on the CNS are complex and not completely understood [190,191]. IFNs are known to have major effects on microglia cells, which may cause a cascade of consequences in other CNS cell types [192]. Remarkably, endogenous and exogenously administered IFNs may exert anti-inflammatory [193] as well as pro-inflammatory effects [194][195][196][197] in models for neurodegenerative and non-neurodegenerative diseases.…”
Section: Molecular Effects Of Ifnsmentioning
confidence: 99%
“…Inflammation affects white matter microstructure via elevating levels of circulating pro-inflammatory cytokines, which increase blood-brain barrier permeability (Stolp et al, 2009;Stolp, Dziegielewska, Ek, Potter, & Saunders, 2005;Varatharaj & Galea, 2017) and can trigger inflammatory processes in the brain (Konsman, Parnet, & Dantzer, 2002). Subsequent neuroinflammation has cascading effects that activate microglia (Sankowski, Mader, & Valdés-Ferrer, 2015), which contribute to white matter pathology in the form of volume reductions and loss of oligodendrocyte precursor cells (Li et al, 2017;McDonough, Lee, & Weinstein, 2017;Stolp et al, 2009). Local white matter damage can, in turn, send cytokine-mediated signals back to the periphery (Chen, Castro, Chow, & Reichlin, 1997;Chen & Reichlin, 1998;Romero, Kakucska, Lechan, & Reichlin, 1996), resulting in a reciprocal relationship between white matter microstructure and immune responses.…”
Section: Introductionmentioning
confidence: 99%